"Down the Rabbit Hole" of Vaccine Misinformation on YouTube: Network Exposure Study - Tang, Lu; Fujimoto, Kayo; Amith, Muhammad (Tuan); Cunningham, Rachel; Costantini, Rebecca A; York, Felicia; Xiong, Grace; Boom, Julie A; Tao, Cui (JMIR Publications, 2021)
BackgroundSocial media platforms such as YouTube are hotbeds for the spread of misinformation about vaccines. ObjectiveThe aim of this study was to explore how individuals are exposed to antivaccine misinformation on YouTube based on whether they start their viewing from a keyword-based search or from antivaccine seed videos. MethodsFour networks of videos based on YouTube recommendations were collected in November 2019. Two search networks were created from provaccine and antivaccine keywords to resemble goal-oriented browsing. Two seed networks were constructed from conspiracy and antivaccine expert seed videos to resemble direct navigation. Video contents and network structures were analyzed using the network exposure model. ResultsViewers are more likely to encounter antivaccine videos through direct navigation starting from an antivaccine video than through goal-oriented browsing. In the two seed networks, provaccine videos, antivaccine videos, and videos containing health misinformation were all found to be more likely to lead to more antivaccine videos. ConclusionsYouTube has boosted the search rankings of provaccine videos to combat the influence of antivaccine information. However, when viewers are directed to antivaccine videos on YouTube from another site, the recommendation algorithm is still likely to expose them to additional antivaccine information.